Long-term benefits in self-reported health status of nasal continuous positive airway pressure therapy for obstructive sleep apnoea. - Jenkinson, C; Davies, R; Mullins, R; Stradling, JR (2001)
Doubt has been expressed about the efficacy of nasal continuous positive airways pressure (NCPAP) therapy for sleep apnoea. Recent evidence from a randomized controlled trial of 1 month duration, suggested that NCPAP therapy can have a substantial impact on subjective and clinical outcomes in the short term, but data was not available to determine whether these effects were sustained over the long term. This study, an extension of the original trial, examined whether the beneficial impacts of NCPAP continued over the longer term. Patients were followed-up 1 month after being placed on active or sub-therapeutic NCPAP. They completed health status measures and a clinical test of sleepiness. After this period, all patients were placed on NCPAP and followed up 5 months later. The beneficial impact of NCPAP on sleep apnoea was sustained on all measures at follow-up. Furthermore, those who had initially been in the sub-therapeutic arm gained scores after 5 months of NCPAP similar to those of the active group. The impact of NCPAP appears sustained in the longer term. Subjective health status instruments have been advocated as important outcome points in randomized trials. This study would support such a use, and shows the important role of patient report in the evaluation of health care.